OPTIMALISASI PERTUMBUHAN DAN PERKEMBANGAN BAYI DENGAN HOME CARE BABY SPA DAN BABY GYM DI MASA PANDEMI - Eka Falentina Tarigan; Eva Ratna Dewi; Siti Nurmawan Sinaga; Marliani Marliani; Cindy Silvia Br. Sitepu (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Based on data from the Basic Health Research (Riskesdas) in 2018, there are 37.2% of children under five in Indonesia experiencing stunting. Public health problems are considered serious if the short prevalence is 30-39 percent and serious if the short prevalence is 40 percent. There are 16% of Indonesian toddlers experiencing developmental disorders, both fine and gross motor development, hearing loss, low intelligence and delays. The purpose of the study was to determine the difference in the effect of the baby gym and baby spa on growth and development. This research is a quasi-experimental research and the design used is pre test post test with control group design. The research subjects consisted of 20 infants in the case group and 20 infants in the intervention group at the Mother's School of the True Mother Foundation in 2019. The effect of the baby gym in increasing growth and development with the paired sample t-test, the results obtained for body weight p value = 0.716, for development p = 0.330 and for body length p value = 0.014. The effect of the baby spa in the intervention group was carried out by paired sample t-test. The results were for weight, p = 0.012, for body length, p = 0.000 and for development, p = 0.001. Differences in the effect of baby gym and baby spa in increasing growth and development in infants with independent sample t test, the results obtained for growth are weight p value = 0.00, for body length p value = 0.021 and for development p value = 0.00 . Ho is rejected and Ha is accepted so that it can be concluded that there is a difference in the effect of baby gym and baby spa in increasing growth and development in infants 9-12 months. Keywords : Baby Gym, Baby Spa, Growth, Development, Baby